Environmental Regulation and Competitiveness - Abay Mulatu; Raymond J.G.M. Florax; Cees A.A.M. Withagen (Tinbergen Institute, 2001)
The potential relationship between domestic environmental regulation and internationalcompetitiveness has evoked various speculations. The common neoclassical train of thought is thatstrict environmental regulation is detrimental to the competitiveness of industry, and that itinduces phenomena such as ecological dumping, ecological capital flight, and regulatory 'chill' inenvironmental standards. A different view is that strict environmental regulation triggers industry'sinnovation potential, and subsequently increases its competitiveness. The impact of environmentalregulation on competitiveness has been analyzed in terms of international capital movements, newfirm formation, and international trade. This paper focuses on a statistically rigorous analysis ofinternational trade studies, using a technique that is known as meta-analysis. The paper presentsa statistically supported evaluation of the literature, in order to assess what the main conclusionsregarding the relationship between environmental regulation and competitiveness are when itcomes to studies on international trade flows. The synthesis of the literature is subsequently usedto present guidelines for future primary research in this area.
Keywords: F18; H30; L50; Q00; 330; environmental policy; strictness; competitiveness; meta-analysis; Umweltpolitik; Internationaler Wettbewerb; Theorie